Successful treatment of Budd-Chiari Syndrome with Rivaroxaban in a six week old Bangladeshi infant - Mukesh Khadga; Ferdous Ara Begum; Mohammad Wahiduzzaman Mazumder; Mohammad Benzamin; Nazmul Ahamed Rony; Abu Zafor Mohammad Raihanur Rahman; Ayesha Siddiqua; Nazmul Hassan; Abu Sayed Mohammad Bazlul Karim (Indonesian Pediatric Society, 2022)
Budd-Chiari syndrome (BCS) is the clinical spectrum presenting with hepatic venous outflow obstruction from the hepatic veins to the junction of the inferior vena cava (IVC) and the right atrium. This syndrome is rare in infants and children, which leads to misdiagnoses or delayed diagnoses. Clinical presentations may be non-specific. A high index of suspicion and imaging findings may help in early diagnosis of this condition. We report a rare case of BCS in a 6-week-old male infant who presented with jaundice and gradual abdominal distension. He was successfully treated with rivaroxaban.